Stayin' alive: Export credit guarantees and export survival - Magnus Lodefalk; Aili Tang; Miaojie Yu (Örebro University School of Business, 2022)
We use survival analysis to analyse the impact of export credit guarantees on firms' export duration using granular Swedish panel data at the firm-country and firm-country-product levels. The estimation results show that firms' export survival substantially increases with guarantees, at both levels. The associations are particularly strong for smaller firms and contracts as well as in trade with riskier markets. The findings have implications for policies to promote long-run export growth.
Keywords: D22; F14; H81; C14; C41; 330; Survival; Exports; Export credit guarantees